Improving Public Policy Advocacy Through the Effective Use of Data - Doyle, Michelle L. (Catholic Education: A Journal of Inquiry and Practice, 2004)
The focus for most consumers of federal education program services is the end product. Of concern to these customers ”“ students, teachers, and principals ”“ are the quality of the service, the timeliness of the service delivery, and the relevance of the services to the particular need. To ensure that federal education programs can be effective for children attending private schools, it is critical to be actively involved in the legislative process. This article explores an attempt to change and improve a federal education program for Catholic and other private school participants, highlighting the key role in the lobbying process played by high quality, timely data.